Best practices for the treatment of metastatic pancreatic adenocarcinoma: the therapeutic landscape in 2017 - Cinar, Pelin; Ko, Andrew H. (Chinese Clinical Oncology, 2017)
The vast majority of patients diagnosed with pancreatic adenocarcinoma have inoperable, most commonly metastatic, disease at the time of initial presentation, at which point systemic therapy becomes the mainstay of treatment. Although survival rates remain very poor in this clinical setting, patients currently have a greater number of therapeutic options available to them than ever before, and consequently individuals are more frequently able to be sequenced through multiple lines of treatment. In this review, we will provide an overview of the current treatment landscape for metastatic pancreatic cancer in 2017, focusing on best practices and the various factors that should be considered in selecting the most appropriate regimen for a given individual. Options for front-line therapy include both infusional 5-fluorouracil, leucovorin, irinotecan, oxaliplatin (FOLFIRINOX) and the combination of gemcitabine plus nab-paclitaxel; however, how to choose between these two regimens can sometimes pose a challenging problem, and some patients may not be suitable candidates for either. For patients who are robust enough to receive second-line therapy (and beyond), the selection of treatment depends in part on their prior treatment exposure; newer drugs such as nanoliposomal irinotecan (nal-IRI) (in combination with infusional 5-fluorouracil and leucovorin) are now approved by the United States Food and Drug Administration (FDA) specifically for use following disease progression on first-line gemcitabine-based therapy. Despite these welcome advances in standard of care treatment, patients should still be encouraged to participate in clinical trials whenever possible.